Microwave Assisted Synthesis of Chromium Substituted Nickel Ferrite Spinel for Oxygen Evolution Reaction - Lal, Basant (2020)
Herein, a simple microwave assisted combustion approach is utilized for the synthesis of nano-sized Cr substituted Ni ferrites (NiCrxFe2-xO4). The as obtained materials were further sintered at 450°C in air and then utilized for physicochemical and electrochemical characterizations. X-ray diffraction (XRD) patterns showing sharp peaks confirmed the formation of single phase cubic spinel structure. TEM image reveals the formation of nanocrystalline particles having size in range of 10-20 nm. Further, the electrocatalytic oxygen evolution reaction (OER) of as-synthesized materials was studied by linear sweep voltammetry in alkaline solution. The OER results showed that co-substitution of Cr in NiFe2O4 matrix improved the electrocatalytic activity of the oxides towards OER. The NiCr0.5Fe1.5O4 shows the best OER performance in 1.0 M KOH solution. It achieved a low overpotential of about 320 mV at 10 mA/cm2 current density, which is comparable to other reported electrocatalysts. Tafel parameters and order of reaction were also in close agreements with literature values. DOI: http://dx.doi.org/10.17807/orbital.v12i3.1507